Gambir Catechins (Uncaria gambir Roxb) Prevent Oxidative Stress in Wistar Male Rats Fed a High-Fat Diet - Mellina Rahmi; Rauza Sukma Rita; Husna Yetti (Majalah Kedokteran Andalas, 2021)
Objective: This study aimed to examine how gambir catechins (Uncaria gambir Roxb) affect serum malondialdehyde (MDA) levels and catalase activity in Wistar white male rats fed a high-fat diet. Methods: This is a true experimental study with a post-test-only control group design. The experiment used 30 rats divided into five groups: a negative control group, a positive control group induced by a high-fat diet, and three treatment groups caused by a high-fat diet and given gambir catechins at doses of 10 mg/kg BW/day, 20 mg/kg BW/day, and 40 mg/kg BW/day for 14 days. The TBARs method measures MDA levels, while the colorimetry method measures catalase activity. One-way ANOVA and Post Hoc Tukey HSD are used to analyze the data. Results: The gambir catechin reduced serum MDA and increased catalase activity in male Wistar strain white rats fed a considerably high-fat diet (p<0.05). Conclusion: In mice fed a high-fat diet, catechin gambir was capable of dealing with oxidative damage.